Isolated fetal horseshoe kidney does not seem to increase the risk for abnormal chromosomal microarray results. (March 2018) - Sagi-Dain, Lena; Maya, Idit; Falik-Zaccai, Tzipora; Feingold-Zadok, Michal; Lev, Dorit; Yonath, Hagit; Kaliner, Ehud; Frumkin, Ayala; Ben Shachar, Shay; Singer, Amihood
Abstract: Objective: To examine the risk for clinically significant chromosomal microarray analysis (CMA) among fetuses with apparently isolated horseshoe kidney. Methods: Data from all CMA analyses performed due to isolated horseshoe kidney reported to the Israeli Ministry of Health between January 2013 and September 2016 were retrospectively obtained from a computerized database. Risk estimation was performed comparing the rate of abnormal CMA findings to the general population, based on a systematic review encompassing 9272 pregnancies with normal ultrasound, and local data cohort of 5541 pregnancies undergoing CMA due to maternal request. Results: Of 82 pregnancies with isolated horseshoe kidney, one loss-of-copy-number variant compatible with 16p13.11 microdeletion syndrome was demonstrated (1.2%). In addition, two variants of unknown significance (VOUS) were detected (2.4%). The relative risk for pathogenic CMA findings among pregnancies with isolated single horseshoe kidney was not significantly different from the control population (1.03–1.39%). Discussion: To our best knowledge, our study is the first report describing the rate of clinically significant CMA findings in fetuses with isolated horseshoe kidney. The detection of one pathogenic CMA findings in our cohort implies that the value of CMA analysis in such pregnancies is similar to the general population.